Associations between Pittsburgh Sleep Quality Index Factors and Health Outcomes in Women with Posttraumatic Stress Disorder - Casement, Melynda D. (2012)
OBJECTIVE: The Pittsburgh Sleep Quality Index (PSQI) is a widely used measure of subjective sleep disturbance in clinical populations, including individuals with posttraumatic stress disorder (PTSD). Although the severity of sleep disturbance is generally represented by a global symptom score, recent factor analytic studies suggest that the PSQI is better characterized by a two- or three-factor model than a one-factor model. This study examined the replicability of two- and three-factor models of the PSQI, as well as the relationship between PSQI factors and health outcomes, in a female sample with PTSD. METHODS: The PSQI was administered to 319 women with PTSD related to sexual or physical assault. Confirmatory factor analyses tested the relative fit of one-, two-, and three-factor solutions. Bivariate correlations were performed to examine the shared variance between PSQI sleep factors and measures of PTSD, depression, anger, and physical symptoms. RESULTS: Confirmatory factor analyses supported a 3-factor model with Sleep Efficiency, Perceived Sleep Quality, and Daily Disturbances as separate indices of sleep quality. The severity of symptoms represented by the PSQI factors was positively associated with the severity of PTSD, depression, and physical symptoms. However, these health outcomes correlated as much or more with the global PSQI score as with PSQI factor scores. CONCLUSIONS: These results support the multidimensional structure of the PSQI. Yet, the global PSQI score has as much or more explanatory power as individual PSQI factors in predicting health outcomes.